Domenico Rea e il Novecento italiano - Caputo, Vincenzo (Orione. Studi e testi di Letteratura italiana, 2023)
It truly would be a mistake to associate Domenico Rea with the critical cliché of the "rediscovered writer." Important bibliographic "clues" (works by and about Rea, have been consistently published in recent decades), which would inevitably direct us towards the mammoth 'proof' of the Meridiano, edited by the late Francesco Durante in 2005. Specific names need not be mentioned here, as they are mostly indicated and discussed in the essays in this volume. Instead, it is important to highlight the corollary derived from this preliminary evidence. If this is the case, if Rea's writing has continued to be read and discussed in different forms and ways over the years, then the question is not so much one of, so as to say - give Rea what is Rea's. Rather, the problem becomes one of verifying the methods, timing, and critical formulas of this continuity. In other words, a reflection on the production of the Neapolitan writer - and setting the ambitious goal of being 'wide-ranging' - must bring to light unfounded spaces, unpublished and rare materials so as to reconstruct friendships and intellectual relationships, to reason as to the longevity of his work and its internal relationships. In recent years, the activities of the 'National Committee for the celebrations of the centenary of his birth', established by Ministerial Decree 220, 17 June 2021, and chaired by Pasquale Sabbatino, have focused on these objectives. Starting from the opening conference "Domenico Rea and Italian Twentieth Century" (Naples, November 9-11, 2021), the proceedings of which are published here, an attempt has been made to transform this centenary into a broader "critical occasion".